Students’ Knowledge Level about Earthquake and Tsunami in Disaster and Non-Disaster Alert School in Banda Aceh - Hasmunir Hasmunir; Muhammad Okta Ridha Maulidian (Proceedings of AICS - Social Sciences, 2017)
Banda Aceh is the worst affected areas by earthquake and tsunami 26 December 2004 that claimed more than 75% of fatalities and also destroyed almost all the buildings in this region. Post-tsunami, many encouragements such as international agencies, local, and government cooperate to rebuild the affected areas including Banda Aceh. Tsunami and Disaster Mitigation Research Center (TDMRC), University of Syiah Kuala, has begun to produce the disaster alert school program (DAS) by reaching out to the prominent stakeholders in creating a community of disaster-resistant character that is the school community. This study was conducted to determine the level of students’ knowledge of the Earthquake and Tsunami on Disaster Alert School and Non-Disaster Alert School in Kuta Raja, Banda Aceh. The population is 4 elementary schools (2 DAS and 2 Non-DAS). Samples were taken 20% of 196 or 40 students for DAS and 40 students for Non-DAS. The method used is the descriptive method and the data collection technique is the questionnaire. Data analysis technique is by calculating the percentage. The results showed that the students of the Disaster Alert School (DAS) answered a few questions correctly with the percentage of correct answers is 46,3%, while students from Non-DAS have 66,3% the correct answer percentage. So the level of students’ knowledge from DAS in Kuta Raja is less than students from Non-DAS had which is classified as enough.